2013
DOI: 10.1063/1.4812733
|View full text |Cite
|
Sign up to set email alerts
|

Growth and electrical properties of spin coated ultrathin ZrO2 films on silicon

Abstract: Ultrathin (<50 nm) zirconium oxide (ZrO2) films are being intensively studied as high-k dielectrics for future metal-oxide-semiconductor (MOS) technology. In this paper, ultrathin ZrO2 films are deposited on silicon substrates by spin on deposition technique and annealed at 700 °C for different duration. The phase formation and morphological study have been performed by x-ray diffraction and scanning electron microscopy, respectively. Electrical properties of the films are investigated. The threshold vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…By going to a small size scale of the field-effect transistor in integrated circuits, the thickness of SiO 2 has to go to the nanometer scale, but the leakage current of SiO 2 is affected because of tunneling effects. In order to avoid this limitation, ultrathin dielectrics with high k , high capacitances, low leakage current densities, smooth surfaces, and high thermal stability have been tested. , The combination of these characteristics allows large charge densities to be induced in the semiconductor and ensures low-voltage operation. , Some of the most studied inorganic dielectrics are aluminum oxide (Al 2 O 3 ), hafnium oxide (HfO 2 ), tantalum oxide (Ta 2 O 5 ), zirconium oxide (ZrO 2 ), and their mixtures. , Among many potential materials, Al 2 O 3 is a desirable gate insulator because of its characteristic properties such as its high dielectric constant (∼9) combined with a large band gap (8.9 eV), low interfacial trap density with semiconductors, compatibility at low temperatures, high breakdown electric field, and amorphous structure after typical processing conditions. ,− In the last years, the performance of amorphous metal oxides produced by solution can be compared with that of oxide semiconductor films developed by physical vapor deposition, but usually an extra annealing process at high temperatures is necessary to induce a condensed and uniform film, which is not compatible with flexible low-cost substrates. A new strategy to reduce the temperature needed for the production of solution-processed metal oxide thin-film transistors (TFTs) by using self-energy-generating combustion chemistry has been introduced recently . The process of solution combustion synthesis (SCS) allows the energy-efficient synthesis of bulk materials such as carbides, III–V semiconductors, metal oxides, refractory nitrides, and intermetallic compounds. One of the advantages of using the SCS method is that there is no need of any special equipment to provide additional heat because of the combustive reaction of the precursor compounds, which produces self-sustaining heat and supplies sufficient energy to decompose all matter to form the metal oxide.…”
Section: Introductionmentioning
confidence: 99%
“…By going to a small size scale of the field-effect transistor in integrated circuits, the thickness of SiO 2 has to go to the nanometer scale, but the leakage current of SiO 2 is affected because of tunneling effects. In order to avoid this limitation, ultrathin dielectrics with high k , high capacitances, low leakage current densities, smooth surfaces, and high thermal stability have been tested. , The combination of these characteristics allows large charge densities to be induced in the semiconductor and ensures low-voltage operation. , Some of the most studied inorganic dielectrics are aluminum oxide (Al 2 O 3 ), hafnium oxide (HfO 2 ), tantalum oxide (Ta 2 O 5 ), zirconium oxide (ZrO 2 ), and their mixtures. , Among many potential materials, Al 2 O 3 is a desirable gate insulator because of its characteristic properties such as its high dielectric constant (∼9) combined with a large band gap (8.9 eV), low interfacial trap density with semiconductors, compatibility at low temperatures, high breakdown electric field, and amorphous structure after typical processing conditions. ,− In the last years, the performance of amorphous metal oxides produced by solution can be compared with that of oxide semiconductor films developed by physical vapor deposition, but usually an extra annealing process at high temperatures is necessary to induce a condensed and uniform film, which is not compatible with flexible low-cost substrates. A new strategy to reduce the temperature needed for the production of solution-processed metal oxide thin-film transistors (TFTs) by using self-energy-generating combustion chemistry has been introduced recently . The process of solution combustion synthesis (SCS) allows the energy-efficient synthesis of bulk materials such as carbides, III–V semiconductors, metal oxides, refractory nitrides, and intermetallic compounds. One of the advantages of using the SCS method is that there is no need of any special equipment to provide additional heat because of the combustive reaction of the precursor compounds, which produces self-sustaining heat and supplies sufficient energy to decompose all matter to form the metal oxide.…”
Section: Introductionmentioning
confidence: 99%
“…The ALPO devices show a leakage current density of ∼4.5×10 −8 A.cm −2 only at -1 MV.cm −1 electric field. Such low leakage current not only meets the criteria for the application of high-performance flash memory devices, but also outperforms other solution processed inorganic dielectrics namely Al 2 O 3 [24], HfO 2 [25], ZrO 2 [26], and TiO 2 [27], which show typical leakage currents ∼10 −5 A.cm −2 , ∼10 −7 A.cm −2 , ∼10 −2 A.cm −2 and ∼10 −5 A.cm −2 respectively at 1 MV cm −1 . This observation for ALPO also ensures that high quality flash memory devices can be fabricated without the need of blocking or tunneling layers.…”
mentioning
confidence: 79%
“…Alternate high-k dielectrics such as TiO 2 , HfO 2 , ZrO 2 , etc. are excellent insulators for transistor applications [24][25][26][27], but do not have the intrinsic charge trapping properties as silicon nitride. Although solution processed HfO 2 has been used to fabricate SONOS type flash memory [1], the devices required the support of additional dielectric layers which were deposited by sophisticated ultrahigh vacuum techniques with high temperature processing steps to improve the memory leakage.…”
mentioning
confidence: 99%
“…Due to the high quality obtained under a mild condition, it is generally used to deposit the relatively thick high k dielectric layer of TFT [41]. It has also been reported that the sol-gel method was used to prepare ultrathin ZrO 2 films for MOSFET [42,43]. For the preparation of thin films by the solution method, attention should be paid to the molar ratio of the precursor solution and the condition of the post-annealing treatment [44], which are crucial to the properties of the films.…”
Section: Sol-gel Methodsmentioning
confidence: 99%